New Bis(imino)pyridine Complexes of Iron(II) and Iron(III), and Their Catalytic Activity in the Mukaiyama Aldol Reaction - Shejwalkar, Pushkar; Rath, Nigam P.; Bauer, Eike B. (Synthesis, 2014)
New iron(II) and iron(III) complexes bearing bis(imino)pyridine ligands were synthesized and successfully applied to the Mukaiyama aldol reaction. The two complexes [FeCl2L] (L = bis(imino)pyridine ligand, 55% isolated yield) and [LFe(μCl)3FeCl3] (76%) were obtained employing FeCl2 and FeCl3 iron sources, respectively, and characterized by elemental analyses, mass spectrometry, IR spectroscopy and, one example, by X-ray diffraction. The two new iron complexes were subsequently employed as catalysts in the Mukaiyama aldol reaction after abstraction of two chlorides by AgSbF6 to obtain the aldol products in 43% to virtually quantitative yield (CH2Cl2 solvent, room temperature, 3.5 to 16 h reaction time). The impact of the oxidation state of the iron center on the reaction rate and the diastereomeric ratios of the products was investigated.
Keywords: aldol reaction; catalysis; homogeneous catalysis; iron; ligands; nucleophilic addition